Processes of crust formation in the early Earth imaged through Hf isotopes from the East Pilbara Terrane - Gardiner, Nicholas; Hickman, A.; Kirkland, C.; Lu, Y.; Johnson, T.; Zhao, J. (Elsevier BV, 2017)
The Pilbara Craton, Western Australia, is one of the best preserved Palaeo- to Mesoarchaean terrains on Earth. The East Pilbara Terrane is the archetypical granite-greenstone belt, the dome-like complexes of which were formed through three major magmatic events. These granite domes are comprised of metamorphosed granitic igneous rocks that exhibit a magmatic evolution from early tonalite-trondhjemite-granodiorite (TTG) rocks towards K-rich granites over the period 3.53–2.83 Ga. Accordingly, East Pilbara has been a focus for workers seeking to constrain early Archaean geodynamic processes. One way to inform on this debate is to interrogate successive igneous supersuites using tools sensitive to magmatic source. We present new zircon Hf and whole-rock Nd isotope data from four major supersuites of the Mount Edgar Dome, of the East Pilbara Terrane. Early ca. 3.45 Ga TTGs exhibit isotopic signatures that imply their partial derivation from existing crust, with addition of some juvenile material. Subsequent Palaeoarchaean magmatic events show a secular trend towards more evolved isotopic signatures, interpreted as a dominance of increasing reworking of existing crust, with only minor addition of new juvenile crust. The implication of this is that these later Palaeoarchaean supersuites were largely derived from the melting of older granitic crust, with mass balance modelling suggesting an input of ca. 20% juvenile (depleted mantle) material. The limited addition of juvenile material and increased reworking of existing crust with time, does not support a model of modern-style subduction, but is consistent with vertical tectonic processes in a volcanic plateau-type setting for the East Pilbara Terrane >3.2 Ga. All Palaeoarchaean Mount Edgar samples resolve to two-stage Hf model ages of ca. 3.7 Ga and Nd model ages of ca. 3.6 Ga. These Eoarchaean model ages support the existence of a cryptic pre-3.5 Ga protocrust, albeit of unknown extent. Analysis of late Mesoarchaean granites yields highly evolved Hf isotope signatures of K-rich monzogranites. This is consistent with a trend in the East Pilbara Terrane from sodic TTG type magmatism in the early Palaeoarchaean to K-rich magmas in the late Mesoarchaean.